Essential Oil Yield Pattern and Antibacterial and Insecticidal Activities of Trachyspermum ammi and Myristica fragrans - Rajgovind Soni; Gaurav Sharma; Nakuleshwar Dut Jasuja (Scientifica)
Two Indian spices, Trachyspermum ammi and Myristica fragrans, were studied for their essential oil (EO) yielding pattern, insecticidal activity, antibacterial activity, and composition. The essential oils (EOs) of T. ammi (1.94±30 mL/100 gm) and M. fragrans (5.93±90 mL/100 gm) were extracted using hydrodistillation method. In Gas Chromatography analysis, the beta-pinene, alpha-pinene, alpha-p-menth-1-en-4-ol, Limonene, and elemicin were found as major constituents of T. ammi essential oil whereas M. fragrans essential oil mostly contains Gamma-Terpinolene, p-Cymene, Thymol, and beta-pinene. The insecticidal activities of EO were demonstrated using LC50 values against Plodia interpunctella and EO of T. ammi was found comparatively more effective than EO of M. fragrans. Further, individual EO and combination of essential oil were examined for antibacterial activity against three Gram (−) bacterial strains (E. coli-MTCC 443, P. vulgaris-MTCC 1771, and K. pneumoniae-MTCC number 7028) and three Gram (+) bacterial strains (S. aureus-MTCC 3381, B. subtilis-MTCC 10619, and B. megaterium-MTCC 2412) by well agar diffusion method. The essential oil in combination (CEO) exhibited higher antibacterial activity as compared with individual essential oils.